Implementasi Progressive Web Apps (PWA) Menggunakan Laravel Dan Vue.Js dalam Pembuatan Aplikasi Penyedia Jasa Freelance - Adriyansah Efendi Noor; Pahrul Irfan (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
Vocational High School or in Indonesian abbreviated as SMK, is a government program that was built with the aim that students can have expertise in certain fields and can be the initial capital for them in looking for work. An accredited educational curriculum and the many practical activities provided to students can also ensure that SMK graduates are ready to enter the workforce. However, in today's world of work, it requires workers who, in addition to having skills, must also have work experience. There are events held by the government regarding Job Vacancy info which are held only a few times a year so that more participants are participating and the unemployment rate in the regions is getting higher. Based on the above problems, the authors provide a solution by creating a